Symmetry-Supported Magnetic Blocking at 20 K in Pentagonal Bipyramidal Dy(III) Single-Ion Magnets - Chen, Yan-Cong; Liu, Jun-Liang; Ungur, Liviu; Liu, Jiang; Li, Quan-Wen; Wang, Long-Fei; Ni, Zhao-Ping; Chibotaru, Liviu F; Chen, Xiao-Ming; Tong, Ming-Liang (Journal of the American Chemical Society, 2016)
Single-molecule magnets (SMMs) that can be trapped in one of the bistable magnetic states separated by an energy barrier are among the most promising candidates for high-density information storage, quantum processing, and spintronics. To date, a considerable series of achievements have been made. However, the presence of fast quantum tunnelling of magnetization (QTM) in most SMMs, especially in single-ion magnets (SIMs), provides a rapid relaxation route and often sets up a limit for the relaxation time. Here, we pursue the pentagonal bipyramidal symmetry to suppress the QTM and present pentagonal bipyramidal Dy(III) SIMs [Dy(Cy3PO)2(H2O)5]Cl3·(Cy3PO)·H2O·EtOH (1) and [Dy(Cy3PO)2(H2O)5]Br3·2(Cy3PO)·2H2O·2EtOH (2), (Cy3PO = tricyclohexyl phosphine oxide). Magnetic characterizations reveal their fascinating SMM properties with high energy barriers as 472(7) K for 1 and 543(2) K for 2, along with a record magnetic hysteresis temperature up to 20 K for 2. These results, combined with the ab initio calculations, offer an illuminating insight into the vast possibility and potential of what the symmetry rules can achieve in molecular magnetism.